Reduction of carbodiimides by a dialumane through insertion and cycloaddition. Issue 47 (11th May 2020) - Xiao, Lin; Chen, Weixing; Shen, Lingyi; Liu, Li; Xue, Yujie; Zhao, Yanxia; Yang, Xiao-Juan
Abstract : Dialumane reacts with carbodiimides, RNCNR (R = Cy, iPr, dipp, t Bu), through insertion, [2+4] cycloaddition and a hydrogen transfer process. Abstract : The dialumane [L 2− Al II –Al II L 2− ] (L = [(2, 6-iPr2 C6 H3 )NC(Me)]2 ; 1) reacts with carbodiimides, RNCNR (R = Cy, iPr), through insertion, [2+4] cycloaddition, and a hydrogen transfer process. However, with the bulkier carbodiimides (R = dipp = 2, 6-iPr2 C6 H3, t Bu), the reactions are sterically controlled and lead to the formamidinate products.